2014
DOI: 10.1002/lary.24912
|View full text |Cite
|
Sign up to set email alerts
|

Impact of resident surgeons on procedure length based on common pediatric otolaryngology cases

Abstract: Background Surgical education remains an important mission of academic medical centers. Financial pressures, however, may favor improved operating room (OR) efficiency at the expense of surgical education. We aim to characterize resident impact on the duration of procedural time using common pediatric otolaryngologic cases which do not necessitate a surgical assistant and assess whether other factors modify the extent to which residents impact OR efficiency. Study Design We retrospectively reviewed resident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 22 publications
3
49
0
Order By: Relevance
“…Others have demonstrated that inclusion of residents in surgical cases increased operative time compared to attending physicians performing the procedure alone. [10][11][12][13] The effect of the duty hour restrictions on patient outcomes in the surgical literature is conflicting. [14][15][16] Studies in general surgery and obgyn suggest that laboratory-based training leads to more rapid improvement in technical skills and that residents who participate in laboratory-based/simulation training achieve greater competency during patient procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Others have demonstrated that inclusion of residents in surgical cases increased operative time compared to attending physicians performing the procedure alone. [10][11][12][13] The effect of the duty hour restrictions on patient outcomes in the surgical literature is conflicting. [14][15][16] Studies in general surgery and obgyn suggest that laboratory-based training leads to more rapid improvement in technical skills and that residents who participate in laboratory-based/simulation training achieve greater competency during patient procedures.…”
Section: Discussionmentioning
confidence: 99%
“…There is also a similar restriction in Brazil, where the weekly working time for STSs is limited to 60 h including patient care, surgical procedures, and theoretical lessons (5). Following the implementation of the ACGME restriction, concern that the education that was received would not be enough emerged in both teachers and students (3,6). The reason for this can be that concern about being confronted with high levels of compensation encountered in malpractice lawsuits and the increase in the cost of professional liability insurance dominated the workload that the existing educational process entailed.…”
Section: Discussionmentioning
confidence: 99%
“…The basic approach to surgical training has been reported to be the master-apprentice relationship defined by Halsted and Osler in the late 1800s. Although educational resources have currently become diversified with training videos, simulations, and skill labs, the basis of surgical training is still the master-apprentice relationship (2)(3)(4)(5)(6). In addition to all skills, such as the power to interpret theoretical knowledge, that all doctors need to have, manual skills, by which they can effectively and safely apply many alternative methods, should also be taught to residents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, although not exclusively for EVD, studies have shown that intraoperative training could often result in longer operation times, higher financial costs, and greater risk of complications. 5,17,19,26 Cadavers are not a viable option for EVD placement, because preservation techniques change the tactile properties of brain tissue and the ventricular system tends to be distorted or collapsed, making cadavers an inadequate substitute for a live patient. Using simulators for surgical training allows residents to develop the necessary motor skills safely and realistically, without impacting patient care.…”
Section: 10mentioning
confidence: 99%